Effects of vertical and horizontal plyometric training on jump performances and sprint force-velocity profile in young elite soccer players - Norgeot, F.; Fouré, A. (European Journal of Applied Physiology, 2024)
Purpose During a soccer match, horizontal acceleration ability during short sprints is determinant for performance. Development of sprint force and velocity qualites have been reported after plyometric training. However, orientation of plyometric training exercises can influence the functional performance. The purpose of this study was to compare the horizontal and vertical orientation of plyometric training on explosiveness performances and sprint force-velocity profile in young soccer players.